2004
DOI: 10.1111/j.0001-5172.2004.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Are there reliable predictors of postoperative pain?

Abstract: Of the many factors that may influence postoperative pain, chronic sleeping difficulties emerge in this population of patients as the strongest determinant of pain at rest. Intraperitoneal surgery and having a relative with a history of pain are the strongest determinants of pain during cough/mobilization. These findings make physiological sense and deserve more attention by anesthesiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 24 publications
4
43
2
2
Order By: Relevance
“…[25][26][27] Baş ka bir ça lış ma da ise tam tersi ne ka dın la rın da ha az ağ rı duy du ğu be lir til miş -tir. 28 Lynch ve ark.…”
Section: Tar Tiş Maunclassified
“…[25][26][27] Baş ka bir ça lış ma da ise tam tersi ne ka dın la rın da ha az ağ rı duy du ğu be lir til miş -tir. 28 Lynch ve ark.…”
Section: Tar Tiş Maunclassified
“…26 In order to improve postsurgical pain management, previous studies have identified several potential predictors of postoperative pain and several preoperative and psychological factors. 12,22,32,41 Among several factors known to affect postsurgical pain, chronic self-reported sleep disturbances before surgery constituted the strongest determinant of pain at rest postoperatively in some surgical patients. 32 Additionally, surgical patients, particularly hospitalized in the Intensive Care Unit (ICU), frequently reported short-term postoperative sleep disturbances/deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…12,22,32,41 Among several factors known to affect postsurgical pain, chronic self-reported sleep disturbances before surgery constituted the strongest determinant of pain at rest postoperatively in some surgical patients. 32 Additionally, surgical patients, particularly hospitalized in the Intensive Care Unit (ICU), frequently reported short-term postoperative sleep disturbances/deprivation. 19,39 These sleep disturbances may result from surgical stress, a disruptive environment (such as noise, lighting, and patient care activities), medical illness itself, and medical treatments (such as respiratory care, drug therapies, and mechanical ventilation).…”
Section: Introductionmentioning
confidence: 99%
“…1 postoperative pain has been found to prolong immobilization, postoperative ileus, sleep disorders, and fatigue, all of which may delay hospital discharge, 2 and is a frequent cause of patient dissatisfaction. 3 Effective postoperative analgesia allowing early mobilization is therefore recognized as a prerequisite for Enhanced Recovery After Surgery programs. 4,5 Thoracic epidural analgesia (EA) has been shown to improve postoperative analgesia after open intra-abdominal surgery than parenteral opioids.…”
mentioning
confidence: 99%